Genetic diversity and population structure of Cirrhinus mrigala revealed by mitochondrial ATPase 6 gene. (19th May 2018) - Das, Sofia Priyadarsani; Swain, Subrat; Jena, Joykrushna; Das, Paramananda
Abstract: The genetic diversity and population structure of Cirrhinus mrigala were studied using partial mitochondrial ATPase 6 gene. 155 individuals were collected from six distant rivers of peninsular India. A total of 11 haplotypes were found with haplotype diversity value of 0.46711 and nucleotide diversity 0.00154 indicating a low degree of genetic divergence among populations. The result of AMOVA analysis also revealed that 97.53% of the genetic variation contained within populations and 2.47% occurred among populations. An overall fixation index was found to be 0.02466 ( p  < .05). Pairwise Fst analysis showed significant genetic differentiation between the Kaveri and rest of the populations. The minimum spanning tree of the haplotype data demonstrated a common ancestral origin of the mrigal populations in peninsular rivers. From the overall results of the present study it may be inferred that mrigal population in peninsular India have low genetic differentiation. This information would be very essential for setting up of genetic improvement programmes, effective management, and conservation of natural genetic resources of mrigal.